Green finance and green growth nexus: Evaluating the role of globalization and human capital - Muhammad Tufail; Lin Song; Zeeshan Khan (Journal of Applied Economics, 2024)
Green finance is one of the emerging research areas, particularly in academia and industries. However, its contribution to green growth remains relatively unexplored. Unlike previous studies, the current research contributes to the existing literature by using green finance as a policy tool for achieving green growth. The method of moment quantile regression is used to investigate the link between green finance and other control variables on green growth in the 19 selected OECD economies from 1990 and 2021. The main findings of the study support the idea that green finance accelerates green growth in the selected countries. Similarly, the results for human capital show a significantly positive relationship with green growth. Additionally, increase in globalization and GDP decrease green growth. To promote green growth and achieve the sustainable environmental goals set by OECD economies, policymakers and regulators must prioritize green finance.
Keywords: 330; Green finance; green growth; MMQR approach; OECD economies